Space Cooling using Active Chilled Beams and Free Cooling by Outdoor Air: A Performance Assessment Based on Simulations in IDA ICE - Gunnemyr, Axel; Hofmann, Fabian (My University, 2024)
Comfort cooling is increasingly vital, particularly with rising ambient temperatures and growing demands for indoor environmental quality, significantly impacting a building’s energy performance. Consequently, there is a need to reduce purchased cooling through the utilization of ambient free cooling sources. This study explores the option of free cooling by outdoor air in a space cooling system using active chilled beams (ACB). The objective of this thesis is to develop a system model in IDA ICE that extract cooling from ambient air by utilizing the air flow of the existing air handling unit, substituting purchased district cooling with free cooling from outdoor air. A typical office building in Gothenburg was simulated with the developed system model to conduct a quantitative evaluation of the system’s energy and economic performance. This study concludes that the system’s performance, both in terms of energy and economics, is not viable for the designed building. While the available cooling capacity during the cooler periods of the year is abundant, the cooling demand for a typical office during this period is not sufficient for the free cooling system to significantly reduce either specific or primary energy usage. A major part of the cooling demand occurs during the summer when the outdoor air temperature is too high for the free cooling system to be effective. This low reduction, combined with a high investment cost, results in an investment that does not show a foreseeable return.
Keywords: Active chilled beams, comfort cooling, energy performance, free cooling, IDA ICE, life-cycle cost, office space, outdoor air